Influence of European Union Directives on the Use of Liquid Biofuel in the Transport Sector. (2017) - Küüt, Arne; Ilves, Risto; Küüt, Keio; Raide, Veljo; Ritslaid, Kaie; Olt, Jüri
Abstract: Replacing traditional fuels with biofuels in the transport sector has been named as one of the measures in the increasingly strict environmental policy of the European Union. The Renewable Energy Sources directive and Fuel Quality Directive stipulate the minimum required amount of biofuel to be added to the motor fuel used in the transport sector. The former directive stipulates that at least 10% of fuel used in the transport sector comes from renewable sources and the latter directive the reduction of greenhouse gas emissions in fuel production by at least 6% by the year 2020. The first obstacle in implementing biofuels is to understand the requirements of the directives. The problem of replacing traditional fuels with biofuels lies in the requirements which are based on energy content and mass, not volume. Measuring by volume is primarily in the interests of entrepreneurs who are involved directly in the production and selling of fuel. At the same time, it is important to know the various effects of these directives on the results of mixing biofuels. Fuel mixtures which do not require extensive alterations of the engines in comparison to the use of 100% biofuels are preferred. Using fuel mixtures allows meeting the requirements of using biofuels whilst incurring lower costs. In order to solve the abovementioned problems, formulas have been prepared to calculate the minimum volume and relative amount of traditional fuel and biofuel in fuel mixtures to meet the requirements of the directives. The relative amounts have been used to prepare sample graphs and to characterise the formation of biofuel ratio in fuel mixture.